KEBIJAKAN DIVIDEN MEMODERASI HUBUNGAN STRUKTUR MODAL DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN - Shabrina, Alifah; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of capital structure and growth opportunity to the firm value with the dividend policy as the moderating variable on the manufacturing companies which are listed in Indonesia Stock Exchange in 2011-2013 periods. The research samples have been selected by using purposive sampling technique and 18 manufacturing companies (54 firms year) which meet the criteria have been obtained as samples. The data analysis technique has been carried out by using multiple linear regressions analysis which is done by using 16 version SPSS program. The regression equation is done by using Moderated Regression Analysis (MRA). Based on the result of the research shows that: (1) Capital structure does not have any influence to the firm value with the regression value shows a unidirectional positive correlation. (2) Growth Opportunity has influence to the firm value and it shows a negative correlation, so the second hypothesis is denied. (3) The dividend policy has negative influence to the firm value, so the third hypothesis is denied. (4) The interaction between the capital structure and the dividend policy with the negative direction and it cannot moderate the influence of the correlation to the firm value. (5) The interaction between growth opportunity and dividend has positive influence and it can moderate the correlation to the firm value. Keywords: Capital Structure, Growth Opportunity, Firm Value and Dividend Policy. ABSTRAK